Development of receptor cell model with oscillation frequency‐dependent on sensor input intensity. Issue 1 (22nd February 2022) - Morishita, Katsuyuki; Kato, Shinya; Takei, Yuki; Saito, Ken
Abstract: This paper developed a receptor cell model that mimics the receptor cells' function of living organisms. The receptor cell model converts the signal input of the sensor into an oscillating pulse waveform. The oscillation frequency of the receptor cell model varies according to the sensory input intensity. First, the authors construct the receptor cell model by discrete circuit. The circuit was described using circuit simulation and compared with the experimental result. Also, we measure the frequency characteristics utilizing a pressure sensor and an optical sensor. The result shows that the receptor cell model could vary from 300 to 600 Hz according to the sensory input intensity. Second, the authors propose the receptor cell model by the integrated circuit. Experimental results showed that the receptor cell model's oscillation frequency changed from 370 to 890 Hz. As a result, the proposal receptor cell model could output the oscillating pulse waveform dependent on sensor input intensity.